1986
DOI: 10.1021/j100280a081
|View full text |Cite
|
Sign up to set email alerts
|

Formamide, a water substitute. 12. Krafft temperature and micelle formation of ionic surfactants in formamide

Abstract: eV for an indirect transition, and 1.24 eV for a direct transition are close to the reported single value of 1.21 eV (again, the mode was not assigned).The occurrence of both an indirect and direct transition is common for the CdIn2VI4 family of materials, and the difference between £ind and £d has been reported to be 0.1 eV for CdIn2Te4.12 Our value of 0.08 eV is close to the 0.1 eV value. We also obtained a value of 0.16 eV for the difference between £ind and £d for p-Hg!n2Te4. It seems that the difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(75 citation statements)
references
References 4 publications
(4 reference statements)
4
71
0
Order By: Relevance
“…Micelle and liquid crystal formation has been reported in solvents such as ethylene glycol (EG) [15], glycerol [2,16,[26][27][28], formamide [4,[17][18][19][20][21]29], and hydrazine [22,23]. The glycol solvents have high cohesive energies and dielectric constants (ε r (EG) = 53 and ε r (PG) = 30), and hydrogenbonding properties, which are believed to be essential requirements for promoting micellization [24].…”
Section: Introductionmentioning
confidence: 99%
“…Micelle and liquid crystal formation has been reported in solvents such as ethylene glycol (EG) [15], glycerol [2,16,[26][27][28], formamide [4,[17][18][19][20][21]29], and hydrazine [22,23]. The glycol solvents have high cohesive energies and dielectric constants (ε r (EG) = 53 and ε r (PG) = 30), and hydrogenbonding properties, which are believed to be essential requirements for promoting micellization [24].…”
Section: Introductionmentioning
confidence: 99%
“…There has recently been much research dealing with the effects of nonaqueous polar solvents on the formation of cationic micelles (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Micel!e or liquid crystal formation has been reported to occur in such solvents as hydrazine (3,4), glycerol (5,6), ethylene glycol (7,8), and formamide (9)(10)(11)(12)(13)(14)(15)(16)(17)(18), where all of the aforementioned solvents have high cohesive energy, dielectric constant, and a high degree of hydrogen bonding. Evans and co-workers (19) have indicated that the ability of a solvent to form hydrogen bonds is a necessary condition of micelle formation.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, the OTAB appears to be a coagel phase in case A. In case B, the OTAB solution exhibits the micellar structure (35°C), although the Krafft point of OTAB is reported as 38°C [24]. This is because the relaxation time to a coagel structure is quite longer than the observation time when the temperature of the solution (case B; 35°C) is close to the Krafft temperature.…”
Section: Relationship Between the Structural Transition Of Surfactantmentioning
confidence: 68%